Pemodelan Sistem Pendukung Keputusan dengan Metode SMART (Simple Multi Attribute Rating Technique) untuk Penjaringan Anggota Organisasi Mahasiswa - Indriani, Cheryllista; Sunardi, S; Zuliarso, Eri (LPPM STIKOM Tunas Bangsa, 2024)
Student Organization is a forum for students to channel their talents and interests, outside of lecture activities. In the organization, students can develop their potential, build relationships, and improve interpersonal skills. In general, to become part of an organization, students need to take part in the selection conducted by the organization's management. An organization in selection has several criteria in accordance with the objectives of the organization, which are expected to help the organization develop well. It is hoped that later it can help the organization develop well. However, in process, the selection is still done manually which takes quite a long time and tends to be subjective. To solve the existing problems, a Decision Support System that helps determine the decision to accept prospective members. The website-based system that was built, using the Simple Multi Attribute Rating Technique (SMART) method. Attribute Rating Technique (SMART) method. The system is built using a decision support system with the Simple Multi Attribute Rating Technique (SMART) technique and is used to handle multi-criteria problems. The decision-making method includes many aspects of criteria in which there are values owned by each alternative for each criterion that is calculated by the weight value. For further research development, the decision-making system using the SMART method can be added to other relevant criteria